Hubungan Asupan Energi Dan Lemak Dengan Status Gizi Pada Remaja Putri Di Pondok Pesantren Ta'mirul Islam Surakarta - Dwi Arifiyanti, Anggit, Nur Lathifah Mardiyati, S.Gz., M.S (2016)
Introduction. Adolescence (10-18 years) is a vulnerable period of nutrition. This is because during adolescence require higher nutritional substances, changes in lifestyle and eating habits which affect their intake and nutritional needs. The results of the initial survey in Islamic Boarding School Ta'mirul Islam Surakarta obtained the prevalence of normal nutritional status in girls was 80%, overweight was 17%, and obese was 3%. Objective. This study aimed to analyze the relationship between energy and fat intakes with nutritional status among female students at Islamic Boarding School Ta'mirul Islam Surakarta. Research methods. This study was an observational research with cross-sectional approach. The subjects in this research were female students at Islamic Boarding School Ta'mirul Islam Surakarta class X and XII in March 2016, amounting to 54 students. The sampling technique used convenience sampling method. Energy and fat intake data were obtained by direct interview to the respondents using Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). Analysis relationships used Spearman Rank Correlation Tests. Results. The majority of girls had low energy intake 38.9%, 18.5% had good intake and 42.6% had high intake of energi and fat intake female students at Islamic Boarding School Ta'mirul Islam Surakarta amounting 20.4% had low intake, 66.7% had good intake and 13.0% had high intake, of fat results correlation test between energy intake and nutritional status of female students obtained value of p = 0.962 and the correlation test results between fat intake and nutritional status of young women obtained value of p = 0.965. Conclusion. There was no relationship between energy and fat intakes with nutritional status in female students. Suggestion. The students are expected to pay attention to the intake, especially the intake of energy in order to suit your needs.